Widespread decline in terrestrial water storage and its link to teleconnections across Asia and eastern Europe - X. Liu; X. Feng; P. Ciais; B. Fu (Hydrology and Earth System Sciences, 2020)
Recent global changes in terrestrial water storage (TWS) and associated freshwater availability raise major concerns about the sustainability of global water resources. However, our knowledge regarding the long-term trends in TWS and its components is still not well documented. In this study, we characterize the spatiotemporal variations in TWS and its components over the Asian and eastern European regions from April 2002 to June 2017 based on Gravity Recovery and Climate Experiment (GRACE) satellite observations, land surface model simulations, and precipitation observations. The connections of TWS and global major teleconnections (TCs) are also discussed. The results indicate a widespread decline in TWS during 2002–2017, and five hotspots of TWS negative trends were identified with trends between −8.94 and −21.79 mm yr −1 . TWS partitioning suggests that these negative trends are primarily attributed to the intensive over-extraction of groundwater and warmth-induced surface water loss, but the contributions of each hydrological component vary among hotspots. The results also indicate that the El Niño–Southern Oscillation, Arctic Oscillation and North Atlantic Oscillation are the three largest dominant factors controlling the variations in TWS through the covariability effect on climate variables. However, seasonal results suggest a divergent response of hydrological components to TCs among seasons and hotspots. Our findings provide insights into changes in TWS and its components over the Asian and eastern European regions, where there is a growing demand for food grains and water supplies.